LEGAL ASSISTANCE FOR ONLINE BUSINESS LICENSE MANAGEMENT THROUGH OSS SERVICES IN CULINARY BUSINESS (DAPUR SI KITING AND NATAN SNACK) - Abdurrakhman Alhakim; Hanifah Ghafila Romadona (ConCEPt - Conference on Community Engagement Project, 2022)
The development era that’s increasing rapidly in our country gives positive impact on society, where many people have established Micro, Small and Medium Entrepreneurship (MSMEs) as a form of community effort to sustain life. However, the number of MSMEs in Indonesia, not all of them have business legality. Basically a business license is a form of approval and permit issued by the competent authority. This form of business license is very important to build up consumer trust to the products that are sold by SME traders, this also makes MSME traders honest about their Products information and ingredient. The implementation of this PkM in collaboration with Dapur Si Kiting and Natan Snack. Both of them hadn’t been registered as a legal SMES. The method used in the implementation of PkM is to provide assistance to partners in registering business legality through the OSS Website. The results obtained from the implementation of this PkM are the successful registration of business legality, as well as obtaining anoutput in the form of a Business Identification Number (NIB). The author hopes that the next PkM implementation can develop this PkM topic